The relationship between work practice environment and work engagement among nurses: The multiple mediation of basic psychological needs and organizational commitment a cross-sectional survey - Ni, Yun-xia; Wen, Ya; Xu, Ying; He, Li; You, Gui-ying (Frontiers in Public Health, 2023)
Background: Previous researchers have demonstrated that the work practice environment influences nurses’ engagement; however, few studies have explored the mechanisms that explain the links between them. Objectives: To examine whether basic psychological needs and organizational commitment mediate the relationship between the work practice environment and work engagement. Methods: A cross-sectional survey was conducted with a sample of 893 nurses from 14 cities in Sichuan Province of China between November 2021 and December 2021. Data were collected online using the Chinese version of the Practice Environment Scale of the Nursing Work Index, Basic Needs Satisfaction in General Scale, Organizational Commitment Scale, and Utrecht Work Engagement Scale. The Pearson correlation analysis and multiple mediation model were used to analyze the data. Results: The Pearson correlation analysis showed that work practice environment, basic psychological needs, and organizational commitment were positively associated with work engagement. The positive relationship between work practice environment and work engagement was mediated by basic psychological needs and organizational commitment (B=0.505, SE=0.032, 95% CI [0.442, 0.566]). Conclusions: The study substantially contributes to the existing knowledge by revealing the mechanisms of fostering work engagement among nurses and explaining why the work practice environment influences work engagement.